The Effect of Structural Configuration on the Effectiveness of Double Pontoon Floating Breakwater: A Review - Muhammad Salman; Sujantoko Sujantoko; Haryo Dwito Armono (International Journal of Marine Engineering Innovation and Research, 2026)
The need for flexible and environmentally friendly coastal protection has driven the development of floating breakwaters (FBs), particularly the double pontoon floating breakwater (DPFB), which offers adaptive capabilities to varying wave conditions. Despite their widespread application, the effectiveness of DPFBs remains highly dependent on structural configuration, highlighting the need for a comprehensive literature review to understand wave attenuation mechanisms and the influence of design parameters on the transmission coefficient (KT) and reflection coefficient (KR). This review examines the fundamental principles of wave structure interaction for floating systems, energy dissipation mechanisms, and analyzes four key parameters that influence system performance: pontoon geometry, porosity, the presence or absence of inter-pontoon connectors, and gap spacing. The findings indicate that pontoon geometry is the dominant factor governing the initial hydrodynamic response, while porosity plays a significant role in creating effective internal energy dissipation. Gap spacing controls wave interference and resonance, whereas connector use affects the system's dynamic stability, though comparative studies on this aspect remain limited. Overall, wave attenuation effectiveness is not determined by a single parameter but by the combined interactions among these four aspects in influencing KT and KR values. This review emphasizes the need for further research on multi-parameter evaluation and the development of more realistic hydrodynamic models to achieve optimal, adaptive DPFB configurations across diverse marine environments.